2019
DOI: 10.1038/s41385-018-0094-4
|View full text |Cite
|
Sign up to set email alerts
|

A dendritic cell-based systemic vaccine induces long-lived lung-resident memory Th17 cells and ameliorates pulmonary mycosis

Abstract: Tissue-resident memory T cells (TRMs) are a novel nonvascular memory T cell subset. Although CD8 + TRMs are well-characterized, CD4 + TRMs-especially lung-resident memory Th17 cells-are still being defined. In this study, we characterized lung-resident memory Th17 cells (lung TRM17) and their role in protection against the highly virulent fungus Cryptococcus gattii. We found that intravenously transferred DCs preferentially migrated to lungs and attracted recipient DCs and led to the induction of long-lived Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 51 publications
(62 reference statements)
1
32
0
Order By: Relevance
“…Our recent study showed that DC-based vaccination induced lung resident memory Th17 cells, which influence the protective effects against highly virulent C . gattii infection [39]. In the DC vaccine, YPD medium-induced CAP60Δ was used as a vaccine antigen to prime BMDCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our recent study showed that DC-based vaccination induced lung resident memory Th17 cells, which influence the protective effects against highly virulent C . gattii infection [39]. In the DC vaccine, YPD medium-induced CAP60Δ was used as a vaccine antigen to prime BMDCs.…”
Section: Discussionmentioning
confidence: 99%
“…BMDCs were prepared as described previously [5,39]. In brief, bone marrow (BM) cells were harvested from the femurs and tibiae of C57BL/6J mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reviews described experimental antifungal vaccines in detail. 11,12) Several veterinary vaccines against dermatomycosis, including Insol Dermatophyton, Biocan-M, and RIVAC Mikroderm, are clinically available. 17,18) Although Cn: C. neoformans; Cg: C. gattii; HK: heat-killed; ND: not determined; ∆cna1: disruptant of gene coding calcineurin A1, avirulent temperature-sensitive mutant; ∆cda1/2/3: disruptant of three genes coding chitin deacetylase, chitosan-deficient avirulent strain; ∆sgl1: disruptant of gene coding sterylglucosidase-1, avirulent strain accumulating sterylglucosides; ∆cap59, ∆cap60: disruptant of capsule synthesis-related gene, acapsular mutant; ZNF2: gene coding the transcriptional factor, zinc finger protein (the overexpression strain forms hyphae in C. neoformans, and this strain strongly induced inflammatory response in the lungs after infection); ura5: mutant of orotidine monophosphate pyrophosphorylase which is uracil auxotrophic and can proliferate in medium containing 5-fluoroorotic acid (5-FOA) (wild-type cryptococcal cells used for immunization cannot grow in the medium and thus cryptococcal cells for immunization and challenge are distinguishable on plates containing 5-FOA); Th1: CD4 + helper T cells producing IFN-γ; Th17: CD4 + helper T cells producing IL-17A; μMT mice: B-cell deficient mice; DR4 mice: humanized mice expressing human HLA-DR4 (DRB*0401) and lacking endogenous mouse MHC class II; Aβ null mice: MHC class II-deficient mice in which CD4 + T cells are absent; Protection (+/−): +=immunization improved survival rates or reduced fungal burdens after challenge.…”
Section: History Of Cryptococcal Vaccinesmentioning
confidence: 99%
“…Previous studies developed many experimental vaccines and investigated vaccine-mediated protective immunity against cryptococcosis. 11,12) We also developed a dendritic cell (DC)-based vaccine against cryptococcosis caused by the highly virulent C. gattii. [13][14][15][16] We demonstrated that the DC vaccine improves the survival rate and ameliorates the fungal burden in the lungs after C. gattii infection and that lung resident-memory Th17 cells (lung TRM17) play a role in the vaccine-mediated protective effect.…”
Section: Introductionmentioning
confidence: 99%